HSIM: a simulation pipeline for the HARMONI integral field spectrograph on the European ELT - Zieleniewski, S; Thatte, N; Kendrew, S; Houghton, R; Swinbank, A; Tecza, M; Clarke, F; Fusco, T (Oxford University Press, 2015)
We present HSIM: a dedicated pipeline for simulating observations with the HARMONI integral field spectrograph on the European Extremely Large Telescope. HSIM takes high spectral and spatial resolution input data-cubes, encoding physical descriptions of astrophysical sources, and generates mock observed data-cubes. The simulations incorporate detailed models of the sky, telescope and instrument to produce realistic mock data. Further, we employ a new method of incorporating the strongly wavelength dependent adaptive optics point spread functions. HSIM provides a step beyond traditional exposure time calculators and allows us to both predict the feasibility of a given observing programme with HARMONI, as well as perform instrument design trade-offs. In this paper we concentrate on quantitative measures of the feasibility of planned observations. We give a detailed description of HSIM and present two studies: estimates of point source sensitivities along with simulations of star-forming emission-line galaxies at $z\sim 2-3$. We show that HARMONI will provide exquisite resolved spectroscopy of these objects on sub-kpc scales, probing and deriving properties of individual star-forming regions.